ISSUES OF EDUCATION AND UPBRINGING IN THE SPIRITUAL HERITAGE OF OUR ANCESTORS - Tokhtayeva, Shakhinabonu (Oriental Journal of History, Politics and Law, 2025)
This article examines issues of Eastern education, the views of our ancestors on education and upbringing using the examples of Alisher Navoi, Amir Timur, and their works.